Livestock Manure and the Impacts on Soil Health: A Review - Natasha Rayne; Lawrence Aula (Soil Systems, 2020)
Soil health is the capacity of the soil to provide an environment for optimum growth and development of plants, while also ensuring the health of animals and humans. Animal manure has been used for centuries as a source of nutrients in agriculture. However, many other soil properties that contribute to soil health are affected when manure is applied. Bulk density, aggregate stability, infiltration, water holding capacity, soil fertility, and biological properties are impacted to various degrees with manure application. The goal of this paper was to compile the research findings on the effects of various livestock manure types on soil fertility, soil physical properties, soil biology and the yield of various cereal crops. Specifically, this paper summarizes results for poultry, cattle, and swine manure used in various cropping systems. Although there are conflicting results in the literature with regards to the effect of manure on various soil properties, the literature offers convincing evidence of beneficial impacts of manure on soil and the growth of crops. The degree to which manure affects soil depends on the physical and chemical properties of the manure itself and various management and environmental factors including rate and timing of application, soil type, and climate.